CURABLE RESIN COMPOSITION, DRY FILM AND CURED PRODUCT THEREOF, AND ELECTRONIC COMPONENTS COMPRISING THE CURED PRODUCT

JP7645186B2Active Publication Date: 2025-03-13TAIYO HOLDINGS CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2021543801
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-09-06
Filing Date
2020-09-02
Publication Date
2025-03-13
Estimated Expiration
2040-09-02

AI Technical Summary

Benefits of technology

【0011】 本発明の硬化性樹脂組成物によると、その硬化物は、優れた耐熱性と、低反り性とを有し、更に、その硬化物における光透過率にも優れる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007645186000001
    Figure 0007645186000001
  • Figure 0007645186000002
    Figure 0007645186000002
Patent Text Reader

Abstract

[Problem] To provide: a curable resin composition which has excellent heat resistance and low warping properties, while enabling the achievement of a cured product having improved light transmittance; a dry film and a cured product of the curable resin composition; and an electronic component which contains the cured product. [Solution] A curable resin composition which is characterized by containing (A) an amide imide resin, (B) a thermosetting resin, (C) a thermal curing accelerator and (D) inorganic particles, and which is also characterized in that the amide imide resin (A) is a reaction product of a tricarboxylic acid anhydride having an aliphatic structure and an isocyanurate-type polyisocyanate that is synthesized from an isocyanate having an aliphatic structure, while having a number average molecular weight of from 500 to 1,000; a dry film and a cured product of the curable resin composition; and an electronic component which contains the cured product. [Selected drawing] None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a curable resin composition, for example, a curable resin composition for an interlayer insulating material used in rewiring or the like of a printed wiring board, a dry film and a cured product thereof, and an electronic part including the cured product. [Background technology]

[0002] As an interlayer insulating material for printed wiring boards, a curable composition containing, for example, an epoxy resin and a phenolic resin as thermosetting components has conventionally been used to improve various properties of the cured material, such as heat resistance (for example, Patent Document 1). [Prior art documents] [Patent documents]

[0003] [Patent Document 1] Patent Publication No. 2001-226464 DISCLOSURE OF THEINVENTION [Problem to be solved by the invention]

[0004] However, when a phenolic resin is used as in Patent Document 1, the curable resin composition, its dry film, and its cured product are colored in a light yellow or light reddish brown color. This is considered to be due to the light yellow or light reddish brown color inherent to the phenolic resin. Even when a polyimide resin is used, if the polyimide skeleton has an aromatic ring, the curable resin composition, its dry film, and its cured product are colored in a light yellow or light reddish brown color, as in the case of using a phenolic resin.

[0005] Therefore, an object of the present invention is to provide a curable resin composition that has excellent heat resistance and low warpage and is capable of improving the light transmittance in the cured product, a dry film containing the same, a cured product thereof, and a printed wiring board containing the cured product. [Means for solving the problem]

[0006] In view of the above object, the present inventors have conducted extensive research and have found that (A) an amide-imide resin; (B) a thermosetting resin; (C) a heat curing accelerator; (D) inorganic particles, The present inventors have found a curable resin composition, characterized in that (A) amide-imide resin is a reaction product between an isocyanurate-type polyisocyanate synthesized from an isocyanate having an aliphatic structure and a tricarboxylic acid anhydride having an aliphatic structure, and has a number average molecular weight of 500 to 1000, and have completed the present invention.

[0007] In the curable resin composition of the present invention, the (B) thermosetting resin is preferably an epoxy compound having a biphenyl skeleton, an epoxy compound having a dicyclopentadienyl skeleton, or a mixture thereof.

[0008] The curable resin composition of the present invention preferably has a light transmittance of 95% or more at 450 nm when formed into a cured coating film having a thickness of 20 μm.

[0009] Furthermore, the curable resin composition of the present invention preferably has a residual stress of less than 25 MPa when formed into a cured coating film.

[0010] Further, another object of the present invention is achieved by a dry film comprising a resin layer constituted by the above-mentioned curable resin composition, a cured product thereof, and an electronic component comprising the cured product. Effect of the Invention

[0011] According to the curable resin composition of the present invention, the cured product has excellent heat resistance and low warpage, and further, the cured product also has excellent light transmittance. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] The curable resin composition of the present invention comprises (A) an amide-imide resin, (B) a thermosetting resin, (C) a heat curing accelerator, and (D) inorganic particles. The (A) amide-imide resin is a reaction product of an isocyanurate-type polyisocyanate synthesized from an isocyanate having an aliphatic structure and a tricarboxylic acid anhydride having an aliphatic structure, and has a number average molecular weight of 500 to 1,000. The curable resin composition of the present invention has the above-mentioned constitution, and the cured product thereof has excellent heat resistance and low warpage, and further, the light transmittance, particularly the visible light transmittance, of the cured product is good. In addition, the curable composition of the present invention has good lamination properties, and the residual stress of the cured product is suppressed. In other words, the curable resin composition of the present invention exhibits good heat resistance upon curing and suppresses the occurrence of warping, and is therefore advantageous in applications such as an interlayer insulating material for printed wiring boards and the like, and an insulating material for rewiring, particularly in applications where a low level of colorability is desired.

[0013] Each of the components of the curable resin composition will be described in detail below.

[0014] [(A) Amide-imide resin] The curable resin composition of the present invention contains (A) an amide-imide resin. The (A) amide-imide resin is produced by reacting an isocyanurate-type polyisocyanate synthesized from an isocyanate having an aliphatic structure with a tricarboxylic anhydride having an aliphatic structure, and one having a number-average molecular weight in the range of 500 to 1000 is used. That is, the (A) amide-imide resin used in the present invention is produced by directly forming an imide bond from the above-mentioned isocyanurate-type polyisocyanate and a tricarboxylic anhydride, and an amide-imide resin having good material stability, reproducibility, and solubility and excellent transparency can be synthesized in comparison with the synthesis via a polyamic acid intermediate in the prior art. In addition, by setting the number-average molecular weight of the (A) amide-imide resin in the range of 500 to 1000, the viscosity becomes relatively low and the resin is easily dispersed, the melt viscosity during lamination decreases, and the lamination property becomes good. In addition, the imide skeleton of the (A) amide-imide resin improves the heat resistance of the curable composition. Both the isocyanurate-type polyisocyanate and the tricarboxylic anhydride have a structure without an aromatic ring structure. As a result, the amide-imide resin according to the present invention obtained has high transparency, and in turn, the cured product obtained from the curable resin composition according to the present invention containing the amide-imide resin also has high transparency.

[0015] [Isocyanurate-type polyisocyanate] (A) The above-mentioned isocyanurate type polyisocyanate, which is used as a raw material for synthesizing the amide-imide resin, is synthesized from an aliphatic isocyanurate, i.e., an aliphatic linear isocyanate (e.g., hexamethylene diisocyanate, trimethylhexamethylene diisocyanate) or an alicyclic isocyanate (isophorone diisocyanate, hydrogenated tolylene diisocyanate, hydrogenated xylene diisocyanate, norbornane diisocyanate, hydrogenated diphenylmethane diisocyanate).

[0016] Specific examples of isocyanurate polyisocyanates include: HDI3N: Isocyanurate-type triisocyanate synthesized from hexamethylene diisocyanate, HTMDI3N: Isocyanurate type triisocyanate synthesized from trimethylhexamethylene diisocyanate. IPDI3N: Isocyanurate triisocyanate synthesized from isophorone diisocyanate. HTDI3N: Isocyanurate type triisocyanate synthesized from hydrogenated tolylene diisocyanate. HXDI3N: Isocyanurate triisocyanate synthesized from hydrogenated xylene diisocyanate. NBDI3N: an isocyanurate-type triisocyanate synthesized from norbornane diisocyanate, and HMDI3N: An isocyanurate-type triisocyanate synthesized from hydrogenated diphenylmethane diisocyanate. The above triisocyanurates may be used alone or in combination.

[0017] The isocyanate used as the raw material of the amide-imide resin (A) is preferably an alicyclic isocyanate, particularly isophorone diisocyanate. By using an alicyclic isocyanate, the Tg of the amide-imide resin (A) is improved, and a curable resin composition containing the amide-imide resin can provide a cured coating film having excellent thermal properties and transparency.

[0018] [Aliphatic tricarboxylic acid anhydrides] (A) Examples of the aliphatic tricarboxylic anhydride, which is another reaction raw material for the amide-imide resin, include alicyclic tricarboxylic anhydrides, such as cyclohexane tricarboxylic anhydride, methylcyclohexane tricarboxylic anhydride, cyclohexene tricarboxylic anhydride, methylcyclohexene tricarboxylic anhydride, etc. Cyclohexane tricarboxylic anhydride is particularly preferably used.

[0019] Cyclohexanetricarboxylic anhydride is represented by the following formula (1):

[0020] [ka] Specific examples thereof include cyclohexane-1,3,4-tricarboxylic acid-3,4-anhydride, cyclohexane-1,3,5-tricarboxylic acid-3,5-anhydride, cyclohexane-1,2,3-tricarboxylic acid-2,3-anhydride, and in particular, cyclohexane-1,3,4-tricarboxylic acid-3,4-anhydride. That is, by using such an aliphatic tricarboxylic acid anhydride as the raw material for the amide-imide resin (A), the heat resistance of the cured product of the present invention is made even more excellent.

[0021] In addition, as a raw material for producing the (A) amide-imide resin, the above-mentioned aliphatic tricarboxylic acid anhydride may be used in combination with a bifunctional dicarboxylic acid compound, for example, an aliphatic or aromatic dicarboxylic acid, such as sebacic acid, phthalic acid, fumaric acid, maleic acid, and acid anhydrides thereof, in some cases.

[0022] When the carboxylic acid component of the tricarboxylic anhydride reacts with the isocyanate component in the isocyanurate polyisocyanate, imide and amide are formed, and the resin of the present invention becomes an amide-imide resin. When the isocyanurate polyisocyanate reacts with the tricarboxylic anhydride, an imide bond is formed from the acid anhydride group and the isocyanate group, and an amide bond is formed from the carboxyl group and the isocyanate group. However, when the tricarboxylic anhydride group and the polyisocyanate group are reacted in such a ratio that the carboxylic acid (carboxyl group) component of the tricarboxylic anhydride remains, the resulting polyamide-imide resin has a carboxyl group. This carboxyl group reacts with a polymerizable group such as an epoxy group of the epoxy resin contained in the curable resin composition of the present invention described later, and forms a crosslinked structure of the cured product. In addition, in the reaction between the tricarboxylic anhydride and the triisocyanate, the above-mentioned two types of reactions, amidation and imidation, are considered, but the reaction rate of imidization is fast, so the tricarboxylic acid selectively forms an imide at the acid anhydride group.

[0023] It is preferable to react an isocyanurate type polyisocyanate synthesized from an isocyanate having an aliphatic structure with a tricarboxylic anhydride having an aliphatic structure so that the ratio [(M1)+(M2)) / (N)] of the molar number of isocyanate groups of the isocyanurate type polyisocyanate synthesized from the isocyanate having an aliphatic structure to the total molar number of the molar number of carboxyl groups (M1) and the molar number of acid anhydride groups (M2) of the tricarboxylic anhydride having an aliphatic structure is 1.1 to 3, because the polarity in the reaction system is high and the reaction proceeds smoothly, no isocyanate groups remain, the stability of the resulting polyimide resin is good, and the amount of remaining tricarboxylic anhydride is small and separation problems such as recrystallization are unlikely to occur. Among them, 1.2 to 2 is more preferable. In the present invention, the acid anhydride group refers to a -CO-O-CO- group obtained by intramolecular dehydration condensation of two carboxylic acid molecules.

[0024] The imidization reaction is preferably carried out by mixing one or more isocyanates having an aliphatic structure with one or more tricarboxylic acid anhydrides in a solvent or without a solvent, and raising the temperature while stirring. The reaction temperature is preferably 50°C to 250°C, and particularly preferably 70°C to 180°C. By setting the reaction temperature at such a temperature, the reaction rate is increased and side reactions and decomposition are less likely to occur. In the reaction, the acid anhydride group and the isocyanate group form an imide group while decarbonating. The progress of the reaction can be tracked by analytical means such as infrared spectrum, acid value, and quantitative determination of isocyanate groups. In the infrared spectrum, the characteristic absorption of the isocyanate group at 2270 cm -1 decreases with the reaction and further increases to 1860cm -1 and 850cm -1 The acid anhydride group, which has a characteristic absorption at 1780cm, is decreased. -1 and 1720cm -1The absorption of the imide group increases as the reaction proceeds. The reaction may be terminated by lowering the temperature while checking the target acid value, viscosity, molecular weight, etc. However, it is more preferable to continue the reaction until the isocyanate group disappears in terms of stability over time, etc. In addition, during or after the reaction, a catalyst, an antioxidant, a surfactant, other solvents, etc. may be added within a range that does not impair the physical properties of the resin to be synthesized.

[0025] The acid value of the amide-imide resin of the present invention is preferably 70 to 210 KOHmg / g, and particularly preferably 90 to 190 KOHmg / g. If it is 70 to 210 KOHmg / g, excellent performance is exhibited as cured physical properties. The amide-imide resin of the present invention is preferably an amide-imide resin that dissolves in a polar solvent that does not contain either a nitrogen atom or a sulfur atom. An example of such an amide-imide resin is a branched amide-imide resin having a branched structure and an acid value of 60 KOHmg / g or more.

[0026] The (A) amide-imide resin in the curable resin composition has a number average molecular weight Mn in the range of 500-1,000, and preferably 700-900. In the present invention, when the (A) amide-imide resin has a number-average molecular weight Mn of 500 or more, the heat resistance of the cured coating film is good, and when the number-average molecular weight Mn is 1,000 or less, the viscosity is relatively low and the resin is easily dispersed, the melt viscosity during lamination is reduced, and the lamination properties are good. In the present invention, unless otherwise specified, the number average molecular weight is determined by gel permeation chromatography (GPC) using polystyrene as a standard. The content of the (A) amide-imide resin is preferably in the range of 30 to 85 mass %, particularly 40 to 70 mass %, based on the total mass of the solid content of the curable resin composition, because the blending amount in this range improves the Tg of the curable resin composition and provides a cured coating film with excellent thermal properties.

[0027] [(B) Thermosetting resin] The curable resin composition of the present invention further contains (B) a thermosetting resin. As the (B) thermosetting resin, for example, an epoxy compound, an oxetane compound, an episulfide compound, particularly a polyfunctional epoxy compound, an oxetane compound, or an episulfide resin having two or more cyclic ether groups and / or cyclic thioether groups in one molecule is used. In addition, known thermosetting resins such as (blocked) isocyanate compounds, particularly polyisocyanate compounds having two or more isocyanate groups or blocked isocyanate groups in one molecule, amine resins such as melamine resins and benzoguanamine resins and their derivatives, bismaleimide, oxazine, cyclocarbonate compounds, and carbodiimide resins are also included. In the present invention, it is preferable to use an epoxy compound, and a polyfunctional epoxy compound is particularly preferably used. The (A) amide-imide resin of the present invention has a carboxyl group and can react with the above-mentioned epoxy compound to relieve the residual stress generated during curing, so that when a cured coating film of the curable resin composition of the present invention is formed on a substrate, warping of the substrate can be suppressed.

[0028] The epoxy resin used may be liquid, solid or semi-solid. Examples of the polyfunctional epoxy compound include bisphenol A type epoxy resin, brominated epoxy resin, novolac type epoxy resin, bisphenol F type epoxy resin, hydrogenated bisphenol A type epoxy resin, glycidylamine type epoxy resin, hydantoin type epoxy resin, alicyclic epoxy resin, trihydroxyphenylmethane type epoxy resin, bixylenol type or biphenol type epoxy resin or mixture thereof, bisphenol S type epoxy resin, bisphenol A novolac type epoxy resin, tetraphenylolethane type epoxy resin, heterocyclic epoxy resin, diglycidyl phthalate resin, tetraglycidyl xylenoylethane resin, naphthalene group-containing epoxy resin, epoxy resin having a dicyclopentadiene skeleton, glycidyl methacrylate copolymer epoxy resin, cyclohexylmaleimide and glycidyl methacrylate copolymer epoxy resin, epoxy-modified polybutadiene rubber derivative, CTBN-modified epoxy resin, etc., but are not limited thereto. As the epoxy resin, preferred are bisphenol A or bisphenol F novolac type epoxy resins, bixylenol type epoxy resins, biphenol type epoxy resins, biphenol novolac type epoxy resins, naphthalene type epoxy resins, biphenyl type epoxy resins (e.g., biphenyl aralkyl type epoxy resins), or mixtures thereof.

[0029] From the viewpoint of improving heat resistance, epoxy resins having an aromatic ring skeleton (for example, a biphenyl skeleton) are preferred, and from the viewpoint of improving transmittance, epoxy resins having a dicyclopentadiene skeleton are preferred.

[0030] Examples of epoxy resins having an aromatic ring skeleton include epoxy resins having a naphthalene skeleton, particularly epoxy resins having an aralkyl type naphthalene skeleton, and epoxy resins having a biphenyl skeleton, particularly biphenyl aralkyl type epoxy resins. Of these, epoxy resins having a naphthalene skeleton have a planar structure of naphthalene, and can reduce the linear expansion coefficient of the cured product and further improve the heat resistance. Examples of commercially available epoxy resins having a naphthalene skeleton include ESN-190 and ESN-360 manufactured by Nippon Steel Chemical Industry Co., Ltd., EPICRON HP-4032, EPICRON, and HP-4032D manufactured by DIC Corporation, and NC-7000L manufactured by Nippon Kayaku Co., Ltd. The epoxy resins having a biphenyl skeleton can also improve the heat resistance and low linear expansion of the cured product of the composition containing the epoxy resin. Commercially available examples of epoxy resins having a biphenyl skeleton include NC-3000, NC-3000-L, NC-3000-H, NC-3001, and NC-2000-L manufactured by Nippon Kayaku Co., Ltd.

[0031] Furthermore, an example of an epoxy resin having an alicyclic skeleton is an epoxy resin having a dicyclopentadiene skeleton. The epoxy resin having an alicyclic skeleton is expected to have a higher glass transition temperature than an epoxy resin having a chain skeleton. Examples of commercially available epoxy resins having a dicyclopentadiene skeleton include EPICLON (registered trademark) HP-7200, HP-7200-H, and HP-7200-L manufactured by DIC Corporation, and XD-1000 manufactured by Nippon Kayaku Co., Ltd.

[0032] The thermosetting resins as described above may be used alone or in combination of two or more kinds. When the (B) thermosetting resin is used, the blending amount is 20 to 60 parts by mass, particularly 30 to 50 parts by mass, per 100 parts by mass of the solid content of the curable resin composition, so that the cured product of the curable resin composition has extremely excellent heat resistance, low residual stress, and low warpage.

[0033] [(C) Heat curing accelerator] The (C) heat curing accelerator used in the present invention can be arbitrarily selected from tertiary amines, tertiary amine salts, quaternary onium salts, tertiary phosphines, imidazole derivatives, or crown ether complexes (e.g., 18-crown-6 / potassium phenoxide, potassium benzoether, KCl, KBr, ammonium acetate, etc.), and these may be used alone or in combination of two or more. In addition, phosphonium ylides can also be used. Examples of tertiary amines include triethylamine, tributylamine, DBU (1,8-diazabicyclo[5.4.0]undec-7-ene), DBN (1,5-diazabicyclo[4.3.0]non-5-ene), DABCO (1,4-diazabicyclo[2.2.2]octane), pyridine, and N,N'-dimethyl-4-aminopyridine. Examples of tertiary amine salts include the U-CAT series manufactured by San-Apro Co., Ltd. Furthermore, quaternary onium salts formed by the addition reaction of tertiary amines or tertiary phosphines with carboxylic acids or highly acidic phenols can also be used as reaction accelerators. These may be formed as quaternary salts before being added to the reaction system, or may be formed in the reaction system by adding each separately. Specific examples include tributylamine acetate obtained from tributylamine and acetic acid, and triphenylphosphine acetate formed from triphenylphosphine and acetic acid. Examples of quaternary onium salts include ammonium salts, phosphonium salts, arsonium salts, stibonium salts, oxonium salts, sulfonium salts, selenonium salts, stannonium salts, and iodonium salts. Particularly preferred are quaternary ammonium salts and quaternary phosphonium salts. Specific examples of quaternary ammonium salts include tetra-n-butylammonium chloride (TBAC), tetra-n-butylammonium bromide (TBAB), tetra-n-butylammonium iodide (TBAI), and tetra-n-butylammonium acetate (TBAAc).Specific examples of the quaternary phosphonium salt include tetra-n-butylphosphonium chloride (TBPC), tetra-n-butylphosphonium bromide (TBPB), tetra-n-butylphosphonium iodide (TBBI), tetraphenylphosphonium chloride (TPPC), tetraphenylphosphonium bromide (TPPB), tetraphenylphosphonium iodide (TPPI), ethyltriphenylphosphonium bromide (ETPPB), and ethyltriphenylphosphonium acetate (ETPPAc). The tertiary phosphine may be a trivalent organic phosphorus compound having an alkyl group or an aryl group having 1 to 12 carbon atoms. Specific examples include triethylphosphine, tributylphosphine, and triphenylphosphine. Examples of the imidazole derivative include imidazole, 2-methylimidazole, 2-ethylimidazole, 2-ethyl-4-methylimidazole, 2-phenylimidazole, 4-phenylimidazole, 1-cyanoethyl-2-phenylimidazole, 1-(2-cyanoethyl)-2-ethyl-4-methylimidazole, etc. Specific examples of commercially available products include Curesol 2MZ-A, 2MZ-OK, 2PHZ, 2P4BHZ, 2P4MHZ, 2E4MZ, etc. manufactured by Shikoku Kasei Co., Ltd. In addition, examples of compounds that aim to improve stability over time include Novacure HX-3721, HX-3748, HX-3741, HX-3088, HX-3722, HX-3742, HX-3921HP, HX-3941HP, and HX-3613 manufactured by Asahi Chiba Co., Ltd. As the phosphonium ylide, any known compound that can be obtained by the reaction of a phosphonium salt with a base can be used, but from the viewpoint of ease of handling, a compound with high stability is preferred.Specific examples include (formylmethylene)triphenylphosphine, (acetylmethylene)triphenylphosphine, (pivaloylmethylene)triphenylphosphine, (benzoylmethylene)triphenylphosphine, (p-methoxybenzoylmethylene)triphenylphosphine, (p-methylbenzoylmethylene)triphenylphosphine, (p-nitrobenzoylmethylene)triphenylphosphine, (naphthoyl)triphenylphosphine, (methoxycarbonyl)triphenylphosphine, (diacetylmethylene)triphenylphosphine, (acetylcyano)triphenylphosphine, (dicyanomethylene)triphenylphosphine, and the like.

[0034] The amount of the (C) heat curing accelerator used is, for example, in the range of 0.1 to 25 mol% relative to 1 mole of epoxy groups, more preferably 0.5 to 20 mol%, and even more preferably 1 to 15 mol%. By using the curing accelerator in an amount of 0.1 mol% or more relative to the epoxy groups, the reaction tends to proceed at a practical rate, while it is common to use an amount of 25 mol% or less from the standpoint of reaction acceleration effect and economic efficiency.

[0035] [(D) Inorganic particles] The curable resin composition of the present invention contains (D) inorganic particles. Specific examples of the filler include non-metallic fillers such as silica, barium sulfate, calcium carbonate, silicon nitride, aluminum nitride, boron nitride, alumina, magnesium oxide, aluminum hydroxide, magnesium hydroxide, titanium oxide, mica, talc, Neuburg silica, and organic bentonite, as well as inorganic particles (D) such as copper, gold, silver, palladium, and silicon. In the curable resin composition of the present invention, these (D) inorganic particles may be used alone or in combination of two or more kinds. In the present invention, it is preferable to use barium sulfate, silica, or both of them.

[0036] In order for the cured product to look transparent, the average particle size of the inorganic particles (D) should be 1 / 2 the wavelength of visible light or less, preferably 200 nm or less, more preferably 150 nm or less, and more preferably 100 nm or less. In the applications of the curable resin composition of the present invention and its cured product, it is preferable that the cured product is transparent or nearly transparent, and for this reason, inorganic particles with an average particle size of 200 nm or less are usually used. In order to obtain a transparent color without coloring, it is preferable that the average particle size of the inorganic particles is 100 nm or less. That is, the smaller the average particle size, the more visible light is transmitted, and the inorganic particles (D) absorb light in the visible region required for coloring and transmit light outside the visible light region, thereby making the inorganic particles (D) transparent.

[0037] The average particle size here is a value measured by a laser diffraction method. Examples of measuring devices using the laser diffraction method include Nanotrac Wave, manufactured by Nikkiso Co., Ltd.

[0038] In addition, when measuring the average particle size of inorganic particles in a cured product, the surface of the cured product is first etched by plasma treatment to make the inorganic particles visible, and then the inorganic particles are observed with a SEM (scanning electron microscope). 2 The diameter of the inorganic particles observed is measured within the range of 100 mm, and the same operation is repeated five times, including other locations, to calculate the average diameter of the inorganic particles. For example, the plasma treatment is performed using a MARCH PLASMA SYSTEM INC AP-1000 device, with power of 500 W, pressure of 300 Torr, gas of Ar, and treatment time of 10 minutes.

[0039] The content of these (D) inorganic particles is 5 to 60 mass % based on the total mass of the solid content of the curable resin composition of the present invention, and preferably 10 to 50 mass %. By appropriately selecting the blending amount according to the type of (D) inorganic particles, it is possible to improve the heat resistance without decreasing the transparency of the cured coating film.

[0040] In the resin composition of the present invention, when silica is used as the inorganic particles (D), the surface of the silica can be treated with a silane coupling agent. This is because it can prevent precipitation or aggregation after dispersion in a liquid, and as a result, it has excellent storage stability. In addition, it can be stably added without aggregation when blending the resin composition, and further, it can improve the wettability between the resin and the particles of the obtained cured product.

[0041] Examples of the organic group contained in the silane coupling agent include a vinyl group, an epoxy group, a styryl group, a methacryloxy group, an acryloxy group, an amino group, a ureido group, a chloropropyl group, a mercapto group, a polysulfide group, an isocyanate group, etc. The silane coupling agent may be used alone or in combination of two or more kinds.

[0042] [Carboxyl group-containing resin] The curable resin composition of the present invention may optionally contain a carboxyl group-containing resin. The carboxyl group-containing resin is a compound having a structure different from that of the above-mentioned (A) amide-imide resin, and it is possible to use a resin that does not contain an amide-imide structure and has a carboxyl group in the molecule. Specific examples thereof include the following (E1) to (E10).

[0043] Specific examples of the non-photosensitive carboxyl group-containing resin include the following compounds (which may be either oligomers or polymers). (E1) A carboxyl group-containing resin obtained by copolymerizing an unsaturated carboxylic acid such as (meth)acrylic acid with an unsaturated group-containing compound such as styrene, α-methylstyrene, lower alkyl (meth)acrylate, or isobutylene.

[0044] (E2) Carboxyl group-containing urethane resins obtained by polyaddition reaction of diisocyanates such as aliphatic diisocyanates, branched aliphatic diisocyanates, alicyclic diisocyanates, and aromatic diisocyanates with carboxyl group-containing dialcohol compounds such as dimethylolpropionic acid and dimethylolbutanoic acid, and diol compounds such as compounds having phenolic hydroxyl groups and alcoholic hydroxyl groups including polycarbonate polyols, polyether polyols, polyester polyols, polyolefin polyols, acrylic polyols, and bisphenol A alkylene oxide adduct diols.

[0045] (E3) A terminal carboxyl group-containing urethane resin obtained by reacting an acid anhydride with the terminal of a urethane resin obtained by polyaddition reaction of a diisocyanate compound such as an aliphatic diisocyanate, a branched aliphatic diisocyanate, an alicyclic diisocyanate, or an aromatic diisocyanate with a diol compound such as a polycarbonate-based polyol, a polyether-based polyol, a polyester-based polyol, a polyolefin-based polyol, an acrylic polyol, or a compound having a phenolic hydroxyl group and an alcoholic hydroxyl group, including a bisphenol A-based alkylene oxide adduct diol.

[0046] (E4) Carboxyl group-containing photosensitive urethane resins obtained by polyaddition reaction of diisocyanates with (meth)acrylates of bifunctional epoxy resins such as bisphenol A type epoxy resins, hydrogenated bisphenol A type epoxy resins, bisphenol F type epoxy resins, bisphenol S type epoxy resins, bixylenol type epoxy resins, and biphenol type epoxy resins, or their partial acid anhydride modified products, carboxyl group-containing dialcohol compounds, and diol compounds.

[0047] (E5) A photosensitive urethane resin containing a carboxyl group, which is terminated with (meth)acrylation by adding a compound having one hydroxyl group and one or more (meth)acryloyl groups in the molecule, such as a hydroxyalkyl (meth)acrylate, during the synthesis of the resin (E2) or (E4) described above.

[0048] (E6) A carboxyl group-containing photosensitive urethane resin having a terminal (meth)acrylation obtained by adding a compound having one isocyanate group and one or more (meth)acryloyl groups in the molecule, such as an equimolar reactant of isophorone diisocyanate and pentaerythritol triacrylate, during the synthesis of the above-mentioned resin (E2) or (E4).

[0049] (E7) A carboxyl group-containing photosensitive resin obtained by reacting a bifunctional or more polyfunctional epoxy compound as described below with (meth)acrylic acid and adding a dibasic acid anhydride such as phthalic anhydride, tetrahydrophthalic anhydride, or hexahydrophthalic anhydride to the hydroxyl group present in the side chain. Here, the epoxy resin is preferably solid.

[0050] (E8) A carboxyl group-containing photosensitive resin obtained by reacting a polyfunctional epoxy compound in which the hydroxyl groups of a bifunctional epoxy resin as described below are further epoxidized with epichlorohydrin with (meth)acrylic acid, and then adding a dibasic acid anhydride to the resulting hydroxyl groups. Here, the epoxy resin is preferably in a solid state.

[0051] (E9) A carboxyl group-containing photosensitive resin obtained by adding a cyclic ether such as ethylene oxide or a cyclic carbonate such as propylene carbonate to a polyfunctional phenol compound such as novolac, partially esterifying the resulting hydroxyl groups with (meth)acrylic acid, and reacting the remaining hydroxyl groups with a polybasic acid anhydride.

[0052] (E10) A carboxyl group-containing photosensitive resin obtained by further adding a compound having one epoxy group and one or more (meth)acryloyl groups in the molecule, such as glycidyl (meth)acrylate, α-methylglycidyl (meth)acrylate, to any of the resins (E1) to (E9).

[0053] (E11) A carboxyl group-containing photosensitive resin obtained by reacting a compound having a plurality of phenolic hydroxyl groups in one molecule, i.e., a polyphenol compound (e.g., phenol novolac, cresol novolac), with an alkylene oxide such as ethylene oxide or propylene oxide to obtain a reaction product such as a polyalcohol resin, with an unsaturated group-containing monocarboxylic acid such as (meth)acrylic acid, and further reacting the obtained reaction product with a polybasic acid anhydride.

[0054] (E12) A carboxyl group-containing photosensitive resin obtained by reacting a polyphenol compound (e.g., phenol novolac, cresol novolac) with a cyclic carbonate compound such as ethylene carbonate or propylene carbonate, reacting the reaction product obtained with an unsaturated group-containing monocarboxylic acid, and reacting the resulting reaction product with a polybasic acid anhydride. In the present invention, photosensitive carboxyl group-containing photosensitive resins having a polyphenol skeleton, such as the above (E11) and (E12), are preferably used.

[0055] The carboxyl group-containing resin may be used alone or in combination of two or more kinds. However, the total mass is preferably 1 part by mass or more and 40 parts by mass or less per 100 parts by mass of the solid content of the (A) amide-imide resin. This increases the number of solvents that can be selected for the curable resin composition, thereby improving workability.

[0056] [Other ingredients] The curable resin composition of the present invention may contain other components in addition to the above components, provided that the effects of the present invention are not impaired. Examples of additives that may be blended include silicone-based and fluorine-based defoamers, leveling agents, heat curing accelerators, heat polymerization inhibitors, ultraviolet absorbers, solvents, silane coupling agents, plasticizers, foaming agents, flame retardants, antistatic agents, antioxidants, antibacterial and antifungal agents, etc.

[0057] In addition, a solvent can be used to adjust the viscosity of the curable resin composition to an appropriate level for application to a substrate or a carrier film. As such a solvent, mainly organic solvents are used, and specific examples thereof include ketones, aromatic hydrocarbons, glycol ethers, glycol ether acetates, esters, alcohols, aliphatic hydrocarbons, and petroleum-based solvents. More specifically, the organic solvents include ketones such as methyl ethyl ketone and cyclohexanone; aromatic hydrocarbons such as toluene, xylene, and tetramethylbenzene; glycol ethers such as cellosolve, methyl cellosolve, butyl cellosolve, carbitol, methyl carbitol, butyl carbitol, propylene glycol monomethyl ether, dipropylene glycol monomethyl ether, dipropylene glycol diethyl ether, and triethylene glycol monoethyl ether; esters such as ethyl acetate, butyl acetate, dipropylene glycol methyl ether acetate, propylene glycol methyl ether acetate, propylene glycol ethyl ether acetate, and propylene glycol butyl ether acetate; alcohols such as ethanol, propanol, ethylene glycol, and propylene glycol; aliphatic hydrocarbons such as octane and decane; and petroleum-based solvents such as petroleum ether, petroleum naphtha, hydrogenated petroleum naphtha, and solvent naphtha. One of these organic solvents may be used alone, or two or more of them may be used in combination.

[0058] The curable resin composition of the present invention may be a liquid type, or may be a dry film type obtained by drying a liquid type resin composition. The liquid type resin composition may be a two-liquid type or the like from the viewpoint of storage stability, but may also be a one-liquid type. Hereinafter, a dry film will be described in detail as one embodiment of the curable resin composition.

[0059] [Dry film manufacturing] The dry film of the present invention has a resin layer obtained by applying the curable resin composition of the present invention onto a film (hereinafter also referred to as a "carrier film") and then drying. The dry film of the present invention can be obtained by diluting the curable resin composition of the present invention with an organic solvent to adjust the viscosity to an appropriate level, applying the composition to a uniform thickness onto a carrier film using a comma coater, blade coater, lip coater, rod coater, squeeze coater, reverse coater, transfer roll coater, gravure coater, spray coater, or the like, and generally drying the composition at a temperature of 50 to 130°C for 1 to 30 minutes. There is no particular restriction on the coating thickness, but the coating thickness after drying may be appropriately set in the range of generally 3 to 100 μm, preferably 5 to 40 μm.

[0060] As the carrier film, a plastic film can be suitably used, and it is preferable to use a plastic film such as a polyester film such as polyethylene terephthalate, a polyimide film, a polyamideimide film, a polypropylene film, a polystyrene film, etc. There is no particular limitation on the thickness of the carrier film, but it is generally appropriately selected in the range of 10 to 150 μm.

[0061] After the curable resin composition of the present invention is applied onto the carrier film and dried, a peelable film (hereinafter also referred to as a "cover film") may be laminated on the surface of the coating film for the purpose of preventing dust from adhering to the surface of the coating film, etc. Examples of the peelable cover film that can be used include polyethylene film, polytetrafluoroethylene film, polypropylene film, surface-treated paper, etc., and any film may be used as long as the adhesive strength between the coating film and the cover film is smaller than the adhesive strength between the coating film and the carrier film when the cover film is peeled off.

[0062] The drying treatment carried out after the curable resin composition of the present invention is applied onto a carrier film is carried out using a hot air circulation drying oven, an IR oven, a hot plate, a convection oven or the like, thereby obtaining a dry film.

[0063] When the curable resin composition is applied directly onto a substrate, examples of the substrate include printed wiring boards and flexible printed wiring boards on which circuits have been preformed, as well as all grades (e.g., FR-4) of copper-clad laminates for high-frequency circuits made of materials such as paper phenol, paper epoxy, glass cloth epoxy, glass polyimide, glass cloth / non-woven epoxy, glass cloth / paper epoxy, synthetic fiber epoxy, fluorine-polyethylene-polyphenylene ether, polyphenylene oxide-cyanate ester, and the like, as well as polyimide films, PET films, glass substrates, ceramic substrates, wafer plates, and the like.

[0064] [Production of cured product] A cured product (cured film) using the curable resin composition of the present invention is produced as follows. That is, first, the curable resin composition is diluted with a solvent as necessary, and then coated on a substrate. The coating film of the curable resin composition is formed by heating the resin layer obtained after evaporating and drying the solvent at a temperature of about 100 to 180°C for 30 to 60 minutes to thermally cure the resin layer, thereby forming a cured coating film.

[0065] The coating method may be any of a dip coating method, a flow coating method, a bar coater method, and a screen printing method.

[0066] The volatilization drying and thermal curing that occur after application can be carried out using a hot air circulation drying oven, IR oven, hot plate, convection oven, etc. (a method in which hot air in the dryer is brought into countercurrent contact with the substrate using a heat source that uses steam for air heating, or a method in which hot air is blown onto the substrate from a nozzle).

[0067] The curable resin composition of the present invention can provide a cured coating film having a thickness of 20 μm with a light transmittance of 95% or more at a wavelength of 450 nm. Such excellent light transmittance is achieved by using the low molecular weight amide-imide resin (A) obtained from the above-mentioned predetermined raw materials in the curable resin composition of the present invention, and in particular by having an aliphatic structure. This allows the cured coating film to be visually recognized as colorless and transparent or nearly colorless and transparent.

[0068] In addition, according to the curable resin composition of the present invention, the residual stress of the cured coating film obtained from the composition can be less than 25 MPa. The reduction in the residual stress of the cured coating film is brought about by the reaction between the (B) thermosetting resin and the carboxyl group-containing resin, particularly when the curable composition of the present invention contains a carboxyl group-containing resin. In addition, when the curable composition contains an epoxy compound as the (B) curable resin in addition to the carboxyl group-containing resin, the residual stress is reduced while maintaining the strength of the coating film, particularly in the cured coating film obtained by the curing reaction between the carboxyl group of the acid anhydride and the epoxy group.

[0069] The curable resin composition of the present invention is applicable to electronic parts. In the present invention, the term "parts used in electronic circuits" refers to active parts such as printed wiring boards, light-emitting diodes, and laser diodes, as well as passive parts such as resistors, capacitors, inductors, and connectors, and the cured coating film of the curable composition of the present invention exhibits the effects of the present invention. The curable resin composition of the present invention is particularly suitable for forming an insulating cured coating for printed wiring boards, and is further suitable for forming permanent insulating films such as coverlays, solder resists, interlayer insulating materials, and insulating materials for forming rewiring layers.

[0070] An electronic component including a cured product obtained from the curable resin composition of the present invention can fully exhibit its functions as an electronic component because the cured product has excellent resolution and heat resistance. In addition, the cured product obtained from the curable resin composition of the present invention has excellent chemical resistance, so that it does not deteriorate or deform due to the chemicals used, even when cleaning with acids or alkalis during the production of a substrate or cleaning with a solvent during mounting, and the precision of the electronic component can be maintained or improved. EXAMPLES

[0071] The present invention will be described in more detail below with reference to examples and comparative examples. The present invention is not limited to the following examples, and "parts" and "%" described below are all based on mass unless otherwise specified.

[0072] [Synthesis of raw materials] [Production of amide-imide resin] Synthesis Example 1: (A) Synthesis of Amide-imide Resin 1 5184g of EDGA (diethylene glycol monoethyl ether acetate), 2070g (3mol) of IPDI3N (isocyanurate type triisocyanate synthesized from isocyanurate diisocyanate: NCO%=18.2) and 1782g (9mol) of cyclohexane-1,3,4-tricarboxylic acid-3,4-anhydride were added to a flask equipped with a stirrer, a thermometer and a condenser, and the temperature was raised to 140°C. The reaction proceeded with foaming. The reaction was carried out at this temperature for 8 hours. The inside of the system became a pale yellow liquid, and measurement of the characteristic absorption by infrared spectroscopy revealed that the characteristic absorption of the isocyanate group was observed at 2270cm. -1 completely disappeared, 1780cm -1 , 1720cm -1 Absorption of imide groups was confirmed. The acid value was 140 KOHmg / g in terms of solid content, and the molecular weight was 800 in terms of polystyrene. The resin concentration was 40 mass%. This resin solution is called amide-imide resin 1 solution.

[0073] Synthesis Example 2: (A') Synthesis of Amide-imide Resin 2 4628 g of EDGA (diethylene glycol monoethyl ether acetate), 2070 g (3 mol) of IPDI3N (isocyanurate-type triisocyanate synthesized from isocyanurate diisocyanate: NCO%=18.2) and 1386 g (7 mol) of cyclohexane-1,3,4-tricarboxylic acid-3,4-anhydride were added to a flask equipped with a stirrer, thermometer and condenser, and the temperature was raised to 140°C. The reaction proceeded with foaming. The reaction was carried out at this temperature for 8 hours. The inside of the system became a pale yellow liquid, and measurement of the characteristic absorption by infrared spectroscopy revealed that the characteristic absorption of the isocyanate group was observed at 2270 cm. -1completely disappeared, and imide group absorption was confirmed at 1780 cm-1 and 1720 cm-1. The acid value was 140 KOHmg / g in terms of solid content, and the molecular weight was 5800 in terms of polystyrene number average molecular weight. The resin concentration was 40 mass%. This resin solution is called amide-imide resin 2 solution.

[0074] Synthesis Example 3: (A") Synthesis of Amide-imide Resin 3 3554g of EDGA (diethylene glycol monoethyl ether acetate), 2070g (3mol) of IPDI3N (isocyanurate type triisocyanate synthesized from isocyanurate diisocyanate: NCO%=18.2) and 1333g (9mol) of 1,2,4-benzenetricarboxylic acid 1,2-anhydride were added to a flask equipped with a stirrer, a thermometer and a condenser, and the temperature was raised to 140°C. The reaction proceeded with foaming. The reaction was allowed to proceed at this temperature for 8 hours. The system turned into a brown liquid, and the characteristic absorption of the isocyanate group at 2270cm-1 was completely disappeared by infrared spectroscopy, and the absorption of the imide group was confirmed at 1780cm-1 and 1720cm-1. The acid value was 140KOHmg / g in terms of solid content, and the molecular weight was 800 in terms of number average molecular weight in terms of polystyrene. The concentration of the resin content was 40% by weight. This resin solution is referred to as an amide-imide resin 3 solution.

[0075] The number average molecular weights of the above amide-imide resins 1 and 2 were measured by gel permeation chromatography (GPC) (polystyrene standard) using the following measuring device and under the following measuring conditions.

[0076] Device name: Waters 2695 Detector: Waters 2414 refractive index (RI) detector Column: Waters, high-speed analytical HSPgel column, HR MB-L, 3μm, 6mm×150mm×2, and Waters, HSPgel column, HR1, 3μm, 6mm×150mm×2 Measurement conditions: Column temperature: 40℃ RI detector temperature setting: 35℃ Developing solvent: Tetrahydrofuran Flow rate: 0.5ml / min Sample volume: 10μl Sample concentration: 0.5wt%

[0077] Synthesis Example 4: Synthesis of carboxyl group-containing resin In an autoclave equipped with a thermometer, a nitrogen introduction device / alkylene oxide introduction device, and a stirrer, 119.4g of novolac cresol resin (manufactured by Showa Polymer Co., Ltd., product name "Shounol CRG951", OH equivalent: 119.4), 1.19g of potassium hydroxide, and 119.4g of toluene were charged, and the system was replaced with nitrogen while stirring, and the temperature was raised by heating. Next, 63.8g of propylene oxide was gradually dropped, and the reaction was carried out for 16 hours at 125-132℃ and 0-4.8kg / cm2. After that, the reaction solution was cooled to room temperature, and 1.56g of 89% phosphoric acid was added and mixed to neutralize the potassium hydroxide, and a propylene oxide reaction solution of novolac cresol resin with a nonvolatile content of 62.1% and a hydroxyl value of 182.2g / eq. was obtained. This product had an average of 1.08 moles of alkylene oxide added per equivalent of phenolic hydroxyl group. 293.0 g of the resulting alkylene oxide reaction solution of the novolac cresol resin, 43.2 g of acrylic acid, 11.53 g of methanesulfonic acid, 0.18 g of methylhydroquinone, and 252.9 g of toluene were charged into a reactor equipped with a stirrer, a thermometer, and an air inlet tube, and reacted at 110°C for 12 hours while blowing air at a rate of 10 ml / min and stirring. 12.6 g of water was distilled off as an azeotrope with toluene produced by the reaction. After that, the reaction solution was cooled to room temperature, neutralized with 35.35 g of 15% aqueous sodium hydroxide solution, and then washed with water. After that, the toluene was distilled off while replacing it with 118.1 g of diethylene glycol monoethyl ether acetate in an evaporator, and a novolac acrylate resin solution was obtained. Next, 332.5 g of the obtained novolac type acrylate resin solution and 1.22 g of triphenylphosphine were charged into a reactor equipped with a stirrer, a thermometer, and an air inlet tube, and 60.8 g of tetrahydrophthalic anhydride was gradually added while blowing air at a rate of 10 ml / min and stirring, and the reaction was carried out at 95 to 101°C for 6 hours. A carboxyl group-containing resin with a solid acid value of 88 mgKOH / g and a solid content of 71% was obtained.

[0078] [Examples 1 to 5 and Comparative Examples 1 to 5] [Preparation of Curable Resin Composition] The components were blended as shown in Table 1, premixed with a stirrer, and then kneaded and dispersed with a three-roll mill to prepare curable resin compositions according to the examples and comparative examples. The blend amounts in the table are shown in parts by mass (solid content equivalent).

[0079] <1. Heat resistance> The curable resin composition was diluted with methyl ethyl ketone to an appropriate viscosity and applied onto a carrier film (polyethylene terephthalate film). This was heated and dried for 30 minutes in a hot air dryer at 80°C to form a curable resin composition layer with a thickness of 20 μm, and a cover film (polypropylene film) was attached onto the coating to obtain a dry film. Thereafter, the cover film was peeled off, and the copper foil was thermally laminated, and the copper foil was heated at 180°C for 60 minutes to be cured. The cured coating film was peeled off from the obtained copper foil with the cured coating film to obtain a cured coating film. The glass transition temperature of the resulting cured coating film was measured under the following conditions. Equipment: Dynamic viscoelasticity measuring device (Seiko Instruments Inc. DMA6100) Measurement temperature: 30~300℃ (5℃ / min) Frequency: 1Hz Glass transition temperature: The maximum value of the measured tan δ is taken as the glass transition temperature. The higher the glass transition temperature, the higher the heat resistance because the elastic change occurs at a high temperature. The evaluation criteria are as follows: ◎: 190℃ or higher ○: 180℃ or higher △: 170℃ or higher ×: Less than 170℃

[0080] <2. Residual stress and wafer warpage> The curable resin composition was diluted with methyl ethyl ketone to an appropriate viscosity and applied onto a carrier film (polyethylene terephthalate film). This was dried by heating for 30 minutes in a hot air dryer at 80°C to form a curable resin composition layer having a thickness of 10 μm, and a cover film (polypropylene film) was attached onto the coating film to obtain a dry film. Meanwhile, the initial warp (average radius of curvature), elastic modulus, thickness, and Poisson's ratio of a dummy silicon wafer used as a substrate were measured in advance. The dry film (one layer) obtained in each Example was thermally laminated onto the above-mentioned wafer at a maximum temperature of 100° C. using a laminator, and then cured by heating at 180° C. for 60 minutes. As a result, a cured coating film was formed on the wafer, and the warpage (average radius of curvature) of the wafer thus obtained was measured. The above average radius of curvature, modulus of elasticity, thickness, and Poisson's ratio were measured using a thin film stress measuring device FLX-2320-s manufactured by Toho Technology Co., Ltd.

[0081] The residual stress was calculated using the following formula. Residual stress = {wafer elastic modulus × (wafer thickness) 2 / (1-wafer Poisson's ratio) x 6 x cured coating thickness} x {1 / curvature radius of wafer after cured coating formation - 1 / initial wafer curvature radius}

[0082] <3. Lamination properties> The curable resin composition was diluted with methyl ethyl ketone to an appropriate viscosity and applied onto a carrier film (polyethylene terephthalate film). This was dried by heating for 30 minutes in a hot air dryer at 80°C to form a curable resin composition layer with a thickness of 30 μm, and a cover film (polypropylene film) was attached onto the coating to obtain a dry film (thickness 15 μm). A double-sided printed wiring board with a copper thickness of 10 μm, L (line: wiring width) / S (space: gap width) = 5 / 5 μm, and an aspect ratio of 2.0 formed in a comb-tooth pattern fine circuit was subjected to a 0.5 μm equivalent etching treatment using MEC's ​​CZ-8101 treatment as a pretreatment. Next, the 15 μm thick dry film prepared above was laminated onto the double-sided printed wiring board with L / S formed after the above treatment using a batch-type vacuum pressure laminator MVLP-500 (manufactured by Meiki Co., Ltd.). The lamination conditions were 5 kgf / cm 2 The laminate was then heated and laminated at 100°C for 1 minute at 1 Torr, and then pressed under a hot plate pressure of 10 kgf / cm 2Leveling was carried out under conditions of 100° C. and 1 minute.

[0083] After lamination, the carrier film was peeled off and visual inspection was performed to check whether air had entered the boundaries between the lines and spaces, causing air bubbles (voids). A: No void was observed. B: Several voids were found. C: The viscosity and elasticity were high, and the resin layer of the dry film was not in contact with the bottom surface of the space on the evaluation board after lamination.

[0084] <4.Transmittance> The curable resin composition was diluted with methyl ethyl ketone to an appropriate viscosity and applied onto a glass substrate. This was heated and dried for 30 minutes in a hot air dryer at 80°C to form a 20 μm thick curable resin composition layer, which was then heated at 180°C for 60 minutes to be cured. A UV / VIS spectrophotometer was used to measure the transmittance, and the transmittance at 450 nm of the glass substrate with the cured coating film was measured using a glass substrate without the cured coating film as a base. Here, the transmittance was evaluated in accordance with ISO 13468 using a UV-visible spectrophotometer (Ubest-V-570DS manufactured by JASCO Corporation) and an integrating sphere device (ISN-470 manufactured by JASCO Corporation). The evaluation criteria are as follows: A: Transmittance is 98% or more B: Transmittance is 95% or more but less than 98% C: Transmittance is 90% or more but less than 95% D: Transmittance is less than 90%

[0085] [Table 1] *The amounts in the table are based on parts by weight.

[0086] Details of the materials listed in the table are given below. Amide-imide resin 1: Synthesized according to Synthesis Example 1 Mn=800 Amide-imide resin 2: Synthesized according to Synthesis Example 2 Mn=5800 Amide-imide resin 3: Synthesized according to Synthesis Example 3 Mn=800 Thermosetting resin 1: Biphenyl-modified epoxy resin (NC-3000, Nippon Kayaku Co., Ltd.) Thermosetting resin 2: Dicyclopentadiene skeleton-containing epoxy resin (EPICLON (registered trademark) HP7200, manufactured by DIC Corporation) Heat curing accelerator 1: Imidazole-based curing agent (Curesol 2MZ-A (manufactured by Shikoku Kasei Co., Ltd.) Heat curing accelerator 2: 2-ethyl-4-methylimidazole (Curesol 2E4MZ (manufactured by Shikoku Kasei Co., Ltd.) Inorganic particle 1: Barium sulfate Sakai Chemical BF-10 (particle size: 100 nm) Inorganic particle 2: Silica Nippon Shokubai Sea Hoster S10 (particle size: 100 nm) Carboxyl group-containing resin: Synthesized according to Synthesis Example 4 Phenolic resin: Phenol novolac resin HF-1H (Meiwa Chemical Industry Co., Ltd., hydroxyl value 105-109g / eq, solid content 65%)

[0087] From the above, it can be said that the curable resin composition of the present invention not only has excellent heat resistance, but also has low residual stress, is less likely to cause wafer warping, has good lamination properties, and further has good light transmittance.

[0088] The present invention is not limited to the configurations and examples of the above-described embodiment, and various modifications are possible within the scope of the gist of the invention.

Claims

1. (A) an amide-imide resin; (B) a thermosetting resin; and (C) a heat curing accelerator; and (D) inorganic particles, The curable resin composition is characterized in that the (A) amide-imide resin is a reaction product of an isocyanurate-type polyisocyanate synthesized from an isocyanate having an aliphatic structure and a tricarboxylic acid anhydride having an aliphatic structure, and has a number average molecular weight of 500 to 900, and the (B) thermosetting resin is an epoxy compound having a biphenyl skeleton, an epoxy compound having a dicyclopentadienyl skeleton, or a mixture thereof.

2. 2. The curable resin composition according to claim 1, which has a light transmittance of 95% or more at 450 nm when formed into a cured coating film having a thickness of 20 μm.

3. 3. The curable resin composition according to claim 1, which has a residual stress of less than 25 MPa when formed into a cured coating film.

4. A dry film comprising a resin layer formed from the curable resin composition according to any one of claims 1 to 3.

5. A cured product obtained by curing the curable resin composition according to any one of claims 1 to 3 or the resin layer of the dry film according to claim 4.

6. An electronic part comprising the cured product according to claim 5.

Citation Information

Patent Citations

  • Curable resin composition

    JP2001226464A

  • Method for producing resin

    JP2010156000A

  • Curable amide-imide resin and method for producing amide-imide resin

    JP2015155500A

  • Curable resin composition, dry film, cured product and electronic component

    JP2018189851A

  • Polyamide-imide resin, and curable resin composition and cured product of same

    WO2015008744A1